Embodied experiences of lived citizenship beyond the European privilege. The case-study of Romanian women farmworkers in eastern Sicily - Massari, Monica; Gatta, Gianluca; Miceli, Simona; Cabras, Federica (Frontiers in Sociology, 2025)
IntroductionThe article examines the conditions of life and agency of Romanian migrant farmworkers in Sicily's agricultural sector, focusing on the migration-citizenship nexus through a gendered, embodied, racialized, and intersectional lens. It aims to shed light on the paradoxes and contradictions still affecting both formal and lived forms of European citizenship regimes.MethodThis qualitative study is based on fieldwork carried out between 2022 and 2024, which included informal meetings, interviews with migrant women, employers, trade unionists, health and social workers, and participant observation in an after-school center for migrant children.ResultsThe results show that Romanian women face multiple vulnerabilities due to poor working and living conditions, physical and social isolation, gender, family situation, and legal status. Their European citizenship paradoxically subjects them to worse conditions than other migrant workers. Despite their precarious situations, these women display agency practices and counteractions in their daily lives, mainly through micro-strategies that might at first glance appear discreet and passive yet, at the same time, are the outcome of their conscious capacity to adapt to potentially unbearable circumstances. They also employ reworking strategies, such as quitting jobs, and occasionally engage in long-term acts of rupture to claim rights and challenge power structures.DiscussionThe analysis contributes to the debate on how structural determinants of oppression and exploitation relate to subjectivity and agency. It explores various forms of counteraction and survival through the concept of lived citizenship, novel ways of experiencing and enacting citizenship within and across different contexts and spaces, both physical and symbolic. While these actions are neither striking nor highly organized or effective in achieving emancipation, they serve as responses and countermeasures within a restrictive system and shed light on migrant women's reflexivity and struggle for autonomy and control over their lives that deserve greater attention.